The fury [book club bag] - Michaelides, Alex, 1977- (Michael Joseph Ltd, 2025)
Spending Easter with Lana Farrar, a reclusive ex-movie star and one of the most famous women in the world, on her idyllic private Greek island, her guests, concealing hatred and desire for revenge, become trapped when the night ends in violence and murder.